2022
DOI: 10.1037/rep0000458
|View full text |Cite
|
Sign up to set email alerts
|

VR-based cognitive rehabilitation for children with traumatic brain injuries: Feasibility and safety.

Abstract: Impact and ImplicationsChildhood traumatic brain injury (TBI) poses significant impairment in children's executive functions (EFs), yet interventions specifically designed for children's EF rehabilitation post-TBI and rigorous clinical trials to establish the safety and efficacy of such interventions remain lacking. Per the ORBIT model, this study served as the Phase II (a-b) of randomized clinical trials to conduct preliminary testing on the feasibility and safety of a novel virtual reality (VR)-based trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We aimed to recruit enough inpatients with ABI to identify all usability problems in the design [54] and the early stage of this self-developed VR tool and to gather sufficient data to estimate the SD of measured outcomes for planning a subsequent larger trial [55]. Recent studies, which involved new-generation headsets, customized VR-based rehabilitation tools, focused on patient needs, tested the system in samples ranging from 11 to 35 patients with ABI, and found that VR was accepted and feasible for rehabilitation [37,38,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to recruit enough inpatients with ABI to identify all usability problems in the design [54] and the early stage of this self-developed VR tool and to gather sufficient data to estimate the SD of measured outcomes for planning a subsequent larger trial [55]. Recent studies, which involved new-generation headsets, customized VR-based rehabilitation tools, focused on patient needs, tested the system in samples ranging from 11 to 35 patients with ABI, and found that VR was accepted and feasible for rehabilitation [37,38,56].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors conducted second-phase trials to effectively evaluate the feasibility and preliminary efficacy of the VR-based intervention. Their primary findings suggest improvements in outcome measures of cognitive functions when the intervention is tailored to address the specific cognitive function, incorporating serious games techniques, using a patient-centered design approach, and administering sessions lasting approximately 30 minutes each [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown that it is an intervention with potential efficacy in moderate to severe TBI and its safety. The intervention group reported adequate VR satisfaction, low levels of physical exertion, and simulator sickness [73].…”
Section: Innovative Approaches In Tbi Rehabilitationmentioning
confidence: 96%
“…Power analyses were conducted in G*Power 3.1 to determine the sample size required for the proposed R00 study. We estimated the long-term intervention effect size to be 0.94 (Cohen’s d ) based on the preliminary data collected from children with moderate/severe TBIs from baseline to follow-up in a pilot study conducted prior to this project [ 28 ]. Using a directional one-tail test (as the intervention is expected to improve EFs) and alpha = 0.05, a total sample size of 30 participants is required to offer a power of 0.80.…”
Section: Interventionsmentioning
confidence: 99%
“…This assessment will be administered immediately (up to 2 weeks) after the completion of the intervention. Although this measure has been used in previous pediatric TBI research its psychometric properties are unknown [ 28 ].…”
Section: Data Collection and Managementmentioning
confidence: 99%